Discovery of 194 Unreported Conopeptides and Identification of a New Protein Disulfide Isomerase in Conus caracteristicus Using Integrated Transcriptomic and Proteomic Analysis - Zhang, Han; Wang, Lei; Qiu, Yinbin; Gong, Fahui; Nong, Baoting; Pan, Xinghua (Frontiers in Marine Science, 2022)
Current ConoServer database accumulates 8,134 conopeptides from 122 species of cone snail, which are pharmaceutically attractive marine resource. However, many more conopeptides remain to be discovered, and the enzymes involved in their synthesis and processing are unclear. In this report, firstly we screened and analyzed the differentially expressed genes (DEGs) between venom duct (VD) and venom bulb (VB) of C. caracteristicus, and obtained 3,289 transcripts using a comprehensive assembly strategy. Then using de novo deep transcriptome sequencing and analysis under a strict merit, we discovered 194 previously unreported conopeptide precursors in Conus caracteristicus. Meanwhile, 2 predicted conopeptides from Consort were verified using liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). Furthermore, we demonstrated that both VD and VB of C. caracteristicus secreted hundreds of different conotoxins, which showed a high diversity among individuals of the species. Finally, we identified a protein disulfide isomerase (PDI) gene, which, functioning for intramolecular disulfide-bond folding, was shared among C. caracteristicus, C. textile, and C. bartschi and was the first PDI identified with five thioredoxin domains. Our results provide novel insights and fuel further studies of the molecular evolution and function of the novel conotoxins.